In2O3-functionalized MoO3 heterostructure nanobelts with improved gas-sensing performance. Issue 56 (24th May 2016) - Zhang, Su; Song, Peng; Zhang, Jia; Li, Zhuoqi; Yang, Zhongxi; Wang, Qi
Abstract : A novel heterostructure with superior TMA-sensing performance were successfully obtained by dispersing In2 O3 nanoparticles on the surfaces of MoO3 nanobelts. Abstract : A novel heterostructure of In2 O3 nanoparticle-functionalized MoO3 nanobelts was synthesized via a simple solution method. The phase purity, morphology and structure of the as-prepared In2 O3 -functionalized MoO3 heterostructure nanobelts were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). To demonstrate the potential applications of such In2 O3 /MoO3 composites, the as-prepared products were used to fabricate a gas sensor that was then investigated for gas-sensing performances. Results of the test showed that the response of In2 O3 nanoparticle-functionalized MoO3 nanobelts against 10 ppm trimethylamine (TMA) is up to 31.69 at the working temperature of 260 °C, which is higher than that of bare MoO3 nanobelts. Moreover, the In2 O3 -functionalized MoO3 heterostructure sensor also exhibits excellent selectivity and rapid response and recovery speed. Such behaviors are attributed to the combination of In2 O3 nanoparticles and uniformly decorated MoO3 nanobelts endowing a fascinating sensing performance for a novel sensing material, which may provide a new strategy to enhance the performance of sensing materials in the application of gas sensors.